So many options, where do we start? An overview of the care transitions literature. Issue 3 (9th November 2015) - Kansagara, Devan; Chiovaro, Joseph C; Kagen, David; Jencks, Stephen; Rhyne, Kerry; O'Neil, Maya; Kondo, Karli; Relevo, Rose; Motu'apuaka, Makalapua; Freeman, Michele; Englander, Honora
Abstract : BACKGROUND: Health systems are faced with a large array of transitional care interventions and patient populations to whom such activities might apply. PURPOSE: To summarize the health and utilization effects of transitional care interventions, and to identify common themes about intervention types, patient populations, or settings that modify these effects. DATA SOURCES: PubMed and Cochrane Database of Systematic Reviews (January 1950–May 2014), reference lists, and technical advisors. STUDY SELECTION: Systematic reviews of transitional care interventions that reported hospital readmission as an outcome. DATA EXTRACTION: We extracted transitional care procedures, patient populations, settings, readmissions, and health outcomes. We identified commonalities and compiled a narrative synthesis of emerging themes. DATA SYNTHESIS: Among 10 reviews of mixed patient populations, there was consistent evidence that enhanced discharge planning and hospital‐at‐home interventions reduced readmissions. Among 7 reviews in specific patient populations, transitional care interventions reduced readmission in patients with congestive heart failure and general medical populations. In general, interventions that reduced readmission addressed multiple aspects of the care transition, extended beyond hospital stay, and had the flexibility to accommodate individual patient needs. There was insufficient evidence on how caregiver involvement, transition to sites other than home, staffing, patient selection practices, or care settings modified intervention effects. CONCLUSIONS: Successful interventions are comprehensive, extend beyond hospital stay, and have the flexibility to respond to individual patient needs. The strength of evidence should be considered low because of heterogeneity in the interventions studied, patient populations, clinical settings, and implementation strategies. Journal of Hospital Medicine 2016;11:221–230. © 2015 Society of Hospital Medicine.